Respuesta :
3x-4y=9
-3x+2y=9
the 3xs would cancel out. then you add the other numbers to get -2y=18. next you would solve for y. -2/18=-9 y=-9. next you would plug y back in to the equation to get -3x+2(-9)=9 next you would symplify to get -3x-18=9. then you would add 18 to 9 to get 27 -3x=27 next you would divide by -3 to get x=-9.
x=-9 and y=-9
-3x+2y=9
the 3xs would cancel out. then you add the other numbers to get -2y=18. next you would solve for y. -2/18=-9 y=-9. next you would plug y back in to the equation to get -3x+2(-9)=9 next you would symplify to get -3x-18=9. then you would add 18 to 9 to get 27 -3x=27 next you would divide by -3 to get x=-9.
x=-9 and y=-9